Wealth and ideology in Italy: The 1923 "quasi abolition" of inheritance tax and Fascists' "middle class politics" - Giacomo Gabbuti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
In summer 1923, pursuant to the 'full powers' granted him by the Parliament to balance the budget, Alberto De Stefani - appointed in October 1922 as Mussolini's Treasury Minister - announced the abolition of inheritance tax. The most iconic act of Fascist 'financial restauration' of 1922-25, the abolition was never proposed before its sudden implementation. Admittedly against 'the universal tendencies of the times,' it provoked surprise and interest, in the country and abroad, but was overlooked by historians. By combining surviving archival evidence, international and Italian media, and a wide survey of other printed sources, the paper offers the first historical reconstruction of this episode - one that clarifies better than other the 'laissez-faire' nature of early Fascism. This new evidence reveals the lobbying activity carried on by pressure groups such as the bankers' association, and a young, proactive association of notaries. The debate surrounding the abolition, and the relevance attributed to it by Fascists before the 1924 election, qualify the episode as an early case of 'middle-class politics'. Indeed, within the recent historiographical revaluation of the early phase of Mussolini's power, the paper argues for the importance of 1920s fiscal policies in coalizing economic elites with the middle classes.
Keywords: D31; D63; H24; N34; P10; 330; inheritance tax; Fascist Italy; interwar Europe; fiscal policy